Comparison of 2 Methods of Debriefing for Learning of Interprofessional Handoff Skills. Issue 1 (7th January 2023) - Ronnebaum, Julie; Jie, Chunfa; Salazar, Kristina
Abstract : Purpose: Interprofessional (IP) handoff communication is imperative for patient safety in high-risk environments. Debriefing is an essential component of the learning process of this skill. Currently, one method of debriefing has not proven more effective than another. Therefore, the purpose of this study was to compare 2 forms of debriefing (face-to-face [F2F] debriefing vs computerized personal reflection) on learning and retention of IP handoff communication. Methods: Fifty-two (n = 52) third-year doctor of physical therapy students completed IP simulated experiences, followed by debriefing. Subjects were divided into 2 groups: ( a ) F2F debriefing (n = 26) and ( b ) computerized personal reflection (n = 26). Observed IP handoff communication behaviors were measured with an assessment tool. Results: Overall IP handoff skills improved from pre- to posttest scores ( P < .05). The F2F debriefing demonstrated greater improvement in the delivery of communication and content skills ( P < .05) than computerized personal reflection debriefing. Conclusion: The F2F debriefing should be included in the training of current and future physical therapists.